Popular Filipino Devotion to the Santo Niño vis-à-vis the Catholic Liturgy and the Theology of the Incarnation - Toledo, John Patrick (Archīum Ateneo, 2021)
In general, popular devotions are seen in a positive light by the Church, not least for their contribution toward the Church’s evangelizing mission. Because they often spring from and are lovingly practiced by the great mass of the faithful, popular devotions increase faith, hope and love, and are a means of inculturating the Christian faith in the local church. For Filipino Catholics, the devotion to the Santo Niño is a much-loved cultural and religious celebration. This thesis explores briefly its historical origin, some of its contemporary expressions, and, more importantly, its necessary liturgical and theological foundations. The study first provides the principles of and guidelines for a healthy devotion to the Santo Niño, giving encouragement to Filipino devotees in its proper practice and in avoiding excesses and abuses. The greater substance of the thesis deals with securing the liturgical—and therefore also the scriptural—basis of the devotion. The liturgy guarantees that the celebration in its popular form will not degenerate into sentimentality, superstition, and the like. Indeed, in the Philippine context more catechesis and liturgical instruction are needed. Moreover, the theology of the Incarnation must be appreciated as providing a firm basis for the devotion, since it gives a Christological and Trinitarian foundation to what might otherwise be treated merely as a socio-cultural phenomenon. The Christian faith proclaims a risen and glorified adult Christ. For all the correctness and legitimacy of a devotion to Christ as a human child, the Church must ceaselessly and carefully give pastoral and theological guidance to devotees and the faithful in general. Nevertheless, the devotion to the Santo Niño in the Church is to be v encouraged and promoted. Ultimately, it serves the Church’s mission: the glorification of God and salvation of humankind.